Modulation of Saccharomyces Cerevisiae DNA Double-Strand Break Repair by Srs2 and Rad51 - Milne, G. T. (1995)
RAD52 function is required for virtually all DNA double-strand break repair and recombination events in Saccharomyces cerevisiae. To gain greater insight into the mechanism of RAD52-mediated repair, we screened for genes that suppress partially active alleles of RAD52 when mutant or overexpressed. Described here is the isolation of a phenotypic null allele of SRS2 that suppressed multiple alleles of RAD52 (rad52B, rad52D, rad52-1 and KlRAD52) and RAD51 (KlRAD51) but failed to suppress either a rad52δ or a rad51δ. These results indicate that SRS2 antagonizes RAD51 and RAD52 function in recombinational repair. The mechanism of suppression of RAD52 alleles by srs2 is distinct from that which has been previously described for RAD51 overexpression, as both conditions were shown to act additively with respect to the rad52B allele. Furthermore, overexpression of either RAD52 or RAD51 enhanced the recombination-dependent sensitivity of an srs2δ RAD52 strain, suggesting that RAD52 and RAD51 positively influence recombinational repair mechanisms. Thus, RAD52-dependent recombinational repair is controlled both negatively and positively.